Fiscal Consequences of Armed Conflict and Terrorism in Low- and Middle-Income Countries - Clements, Benedict; Bhattacharya, Rina.; Chakravarti, Shamit; Gupta, Sanjeev (Washington, D.C. : International Monetary Fund, 2002)
This paper analyses the fiscal effects of armed conflict and terrorism on low- and middle-income countries. An analysis of 22 conflict episodes shows that armed conflict is associated with lower growth and higher inflation, and has adverse effects on tax revenues and investment. It also leads to higher government spending on defense, but this tends to be at the expense of macroeconomic stability rather than at the cost of lower spending on education and health. Our econometric estimates are consistent with the hypothesis that conflict and terrorism have a significant negative impact on growth through changes in the composition of government spending. On the revenue side, the fiscal accounts are affected only through reduced real economic activity. Thus there is potential for a sizable "peace dividend" for countries that are able to resolve conflict and terrorism.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet